Meningkatkan kecerdasan interpersonal melalui permainan tradisional trompa batok kelapa pada anak Kober PAUD Akhlak Mulia Kabupaten Lebong - Rini Purwasi (Early Childhood Research and Practice, 2021)
The purpose of this study is to determine the increase in interpersonal intelligence through the traditional game of coconut shell shoes at PAUD AKHLAK MULIA, Lebong Regency, to determine whether through the use of coconut shell shoes traditional games can improve interpersonal intelligence of children at PAUD AKHLAK MULIA Lebong Regency. Classroom Action Research (CAR), which focuses on classroom situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were 15 children of PAUD AKHLAK MULIA Lebong Regency. Data collection techniques used were observation and documentation methods. The data analysis was carried out in a descriptive qualitative-quantitative manner with the emphasis being used to determine the improvement in the process expressed in a predicate, while quantitative data analysis was used to determine the increase in results using a percentage. The conclusion of this research is that interpersonal intelligence through the traditional game of coconut shell shoes in playgroup of PAUD AKHLAK MULIA, Lebong Regency is developing very well.